Analisis Pelanggan Dalam Pembelian dan Pemakaian Fast Fashion (UNIQLO) Dalam Kalangan Mahasiswa - Tashella Nazha; Anisa Arlinda Putri; Syamsul Hidayat (Institut Nalanda, 2024)
The purpose of this study is to analyze customers in purchasing and using the Uniqlo fast fashion brand among students. The total respondents in the research that can be processed are 101 respondents. The criteria for these respondents are all students at Bina Bangsa University semester 5 classes A, B, C. The analysis technique used is descriptive respondent analysis technique and multiple linear analysis technique. The results of this study indicate that Uniqlo consumers, both men and women pay attention to the image of the Uniqlo brand in choosing to buy their products because of their quality. Furthermore, Uniqlo also has a sufficient number of products. The price of Uniqlo products is also quite affordable because Uniqlo takes raw materials directly from the manufacturer. Uniqlo products can also be used in the long term.